Safety of transcranial direct current stimulation in a patient with deep brain stimulation electrodes - Aline Iannone; Nasser Allam; Joaquim P. Brasil-Neto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Transcranial direct current stimulation (tDCS) has been investigated in movement disorders, making it a therapeutic alternative in clinical settings. However, there is still no consensus on the most appropriate treatment protocols in most cases, and the presence of deep brain stimulation (DBS) electrodes has been regarded as a contraindication to the procedure. We recently studied the effects of cerebellar tDCS on a female patient already undergoing subthalamic nucleus deep brain stimulation (STN-DBS) for generalized dystonia. She also presented with chronic pain and depression. With STN-DBS, there was improvement of dystonia, and botulinum toxin significantly reduced pain. However, depressive symptoms were worse after STN-DBS surgery. Methods: Neuromodulation with 2 mA anodal cerebellar tDCS was initiated, targeting both hemispheres in each daily 30 minute session: 15 minutes of left cerebellar stimulation followed by 15 minutes of right cerebellar stimulation. The DBS electrodes were in place and functional, but the current was turned off during tDCS. Results: Although our goal was to improve dystonic movements, after 10 tDCS sessions there was also improvement in mood with normalization of Beck Depression Inventory scores. There were no complications in spite of the implanted STN-DBS leads. Conclusion: Our results indicate that tDCS is safe in patients with DBS electrodes and may be an effective add-on neuromodulatory tool in the treatment of potential DBS partial efficacy in patients with movement disorders.